Gestión comercial en los productos lácteos elaborados en los talleres agroindustriales de la ESPAM-MFL - Ganchozo Vera, Antonio David (2024)
The objective of this project is to propose a commercial management system to strengthen the sales strategies of dairy products produced in the agro-industrial workshops at ESPAM-MFL. A bibliographic research was applied accompanied by descriptive, deductive, synthetic analytical, meta-analysis and Delphi methods; techniques such as: interview, SWOT, surveys, bibliographic review; and, tools such as the interview guide, questionnaire, SPSS software and test W Kendall. The research was carried out in three phases; the first, carry out a diagnosis of the marketing of dairy products from the ESPAM-MFL agro-industrial workshops to determine the current situation; the second, identify the elements of a commercial management system for its application in the agro-industrial workshops at ESPAM-MFL; the third, to structure a commercial management system that contributes to sales strategies for the improvement of the marketing processes of dairy products of the ESPAM-MFL agro-industrial workshops. Given their execution, the results indicated: the agroindustrial workshops do not have a commercial management system that allows them to self-manage; there is significant potential demand in the Chone, Junín, Calceta and Tosagua markets; and, elements were found that would allow the workshops to have an alternative to be able to market their products. Also, a proposal for a commercial management system was structured where guidelines for the operation of the system were presented to provide a broader understanding of the elements it has.